Assessment of Nitric oxide Linked Atherosclerosis in Surgically Induced Type I and Streptozocin Induced Type II Diabetes Model Goats - Harish Chandra Neupane, Dr (International Journal of Pharmaceutical & Biological Archive, 2012)
Assessment of Nitric oxide Linked Atherosclerosis in Surgically Induced Type I and Streptozocin Induced Type II Diabetes Model Goats